Analysis of ultrasonographic and hystopathologic features of placental invasiveness in Vitro Fertilization (IVF) pregnancies: a prospective study. (12th December 2022) - Capriglione, Stella; Ettore, Carla; Terranova, Corrado; Plotti, Francesco; Angioli, Roberto; Ettore, Giuseppe; Gulino, Ferdinando Antonio
Abstract: Purpose: In Vitro Fertilization (IVF) techniques make up 1.5–5% of all births in developed countries. These pregnancies are characterized by implantation and functional alterations of the placenta, higher incidence of multiple pregnancies, higher incidence of hypertensive syndromes and pre and post partum hemorrhage (PPH). Methods: Since January 2017 to May 2018 all single IVF pregnancies coming to San Camillo Hospital were considered prospectively for routine pregnancy checks until delivery and compared with a control group of spontaneous pregnancies. Each patient underwent to an obstetrical ultrasound of the third trimester at our clinic, with particular attention on the study of the placenta. Birth modalities, type and timing of third stage of labor, peri and post-partum complications were recorded. Results: We had a higher incidence of cesarean sections in the IVF group (85% versus 25%) and peri and post-partum complications (38% versus 5%). We recorded a statistically significant difference of reduction in IVF pregnancies of VI ( p = .0039) and VFI ( p = .0043), while the FI index was not statistically significant in the two study groups ( p = .4351). Conclusion: Despite the small sample size of our study, our data follow the trend of scientific literature, with an effective increase in placental anomalies in IVF pregnancies compared to healthy controls.